1989
DOI: 10.1182/blood.v73.5.1113.bloodjournal7351113
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the expression of alkaline phosphatase mRNA in chronic myelogenous leukemia and paroxysmal nocturnal hemoglobinuria polymorphonuclear leukocytes

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) and the stable phase of chronic myelogenous leukemia (CML) are the two hematological conditions known to be associated with low levels of leukocyte alkaline phosphatase (LAP) activity in peripheral blood polymorphonuclear cells (PMN). LAP mRNA levels were determined in PMN from PNH and CML patients by RNA blotting analysis. In CML, LAP mRNA is undetectable, suggesting either decreased transcription or rapid degradation of the message. Contrarily, in PNH normal or high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…In addition, with this method, we measured LAP protein in whole blood samples obtained from normal volunteers as well as patients suffering from preleukaemic and leukaemic diseases associated with lower and higher than normal levels of LAP enzymatic activity. As expected, neutrophilic granulocytes obtained from PNH (Rambaldi et al, 1989) and CML (Rambaldi et al, 1989 patients were characterized by a very small number of LAP-positive neutrophils with a limited amount of LAP expression on each individual cell. The data obtained in PNH granulocytes demonstrated that the defect in LAP enzymatic activity, typical of this disease, was due to a defective export of the corresponding protein to the plasma membrane and not to mutations affecting the catalytic activity of the polypeptide.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, with this method, we measured LAP protein in whole blood samples obtained from normal volunteers as well as patients suffering from preleukaemic and leukaemic diseases associated with lower and higher than normal levels of LAP enzymatic activity. As expected, neutrophilic granulocytes obtained from PNH (Rambaldi et al, 1989) and CML (Rambaldi et al, 1989 patients were characterized by a very small number of LAP-positive neutrophils with a limited amount of LAP expression on each individual cell. The data obtained in PNH granulocytes demonstrated that the defect in LAP enzymatic activity, typical of this disease, was due to a defective export of the corresponding protein to the plasma membrane and not to mutations affecting the catalytic activity of the polypeptide.…”
Section: Discussionsupporting
confidence: 78%
“…High levels of the enzyme have been observed in the neutrophilic granulocyte during infection, pregnancy, and in various pre-leukaemic conditions, such as Fanconi anaemia and polycythaemia vera (PV) (McComb et al, 1979). In contrast, during the stable phase of CML and paroxysmal nocturnal haemoglobinuria (PNH), a specific defect in the expression of neutrophilic LAP, was observed (Rambaldi et al, 1989). Determination of LAP in peripheral blood neutrophils is diagnostically useful and it is a routine clinical laboratory procedure, which is performed with a semiquantitative assay known as the LAP score (Beutler, 1995;Hayhoe & Quaglino, 1958).…”
mentioning
confidence: 99%
“…In addition, although the function of LAP is not yet known, the presence of mature granulocytes negative for the expression of both the surface and the cytoplasmic form of the protein, suggests that in normal myeloid differentiation LAP does not play a necessary role in the release of mature granulocytes from the bone morrow into the blood stream. We and others previously showed that G-CSF regulates LAP mRNA expression in normal and CML granulocytes (Rambaldi et al, 1989(Rambaldi et al, , 1990Sato et al, 1991). In this study we have provided evidence that pharmacological doses of G-CSF increase in vitro the cell surface expression of LAP protein in normal granulocytes.…”
Section: Discussionsupporting
confidence: 64%
“…The peculiar pattern of LAP expression in CML neutrophils might help in explaining the normal physiology of this enzyme. Indeed, the chronic phase of CML is typically associated with a marked reduction of LAP enzymatic activity as a consequence of LAP mRNA deficiency (Rambaldi et al, 1989). These defects can be corrected in vitro after incubation of CML granulocytes with G-CSF (Yuo et al, 1987;De Renzo et al, 1990;Rambaldi et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation